The Letters of Thomas Merton and Victor and Carolyn Hammer : Ad Majorem Dei Gloriam - Holbrook, Paul Evans, 1949-; Scutchfield, F. Douglas (Book collections on Project MUSE., 2014)
Poet, social justice advocate, and theologian Thomas Merton (1915--1968) is arguably the most influential American Catholic author of the twentieth century. In his short lifetime, he penned over seventy books and maintained a brisk correspondence with colleagues around the globe. However, many Merton scholars and fans remain unaware of the significant body of letters that were exchanged between the Trappist monk and Victor and Carolyn Hammer. Unable to leave his home at the Abbey of Gethsemani except on special occasions, Merton developed a unique friendship with this couple from nearby Lexingt.